Poverty Traps, Aid, and Growth - Kraay, Aart; Raddatz, Claudio (World Bank, Washington, DC, 2012)
The authors examine the empirical evidence in support of the poverty trap view of underdevelopment. They calibrate simple aggregate growth models in which poverty traps can arise due to either low saving or low technology at low levels of development. They then use these models to assess the empirical relevance of poverty traps and their consequences for policy. The authors find little evidence of the existence of poverty traps based on these two broad mechanisms. When put to the task of explaining the persistence of low income in African countries, the models require either unreasonable values for key parameters, or else generate counterfactual predictions regarding the relations between key variables. These results call into question the view that a large scaling-up of aid to the poorest countries is a necessary condition for sharp and sustained increases in growth.